Factors affecting exit intentions from dairy farming in the Pampas region of Argentina - Laura Beatriz Gastaldi; Alejandro Juan Galetto; Ignacio Raúl Pace Guerrero (Economía Agraria y Recursos Naturales)
This article examines the factors which explain exit from dairy farming in the Pampas region of Argentina. A representative sample of dairy farms was used, of which 12 % indicated their intention to exit in the next five years. High technical efficiency and the existence of a successor reduce the likelihood of exit dairy farming; while age of farmer, hired labor, and climate risk exposure are positively associated with exit intentions. The small dairy farms are more prone to exit than large ones, albeit with a smaller marginal effect.